The Theology of Spirituality: Its Growing Importance Amid the Transformations of the Modern World and the Church - Rybicki, Adam (Verbum Vitae, 2020)
This article raises issues surrounding the theology of spirituality as a relatively new theological focus. It argues that, faced with a changing world and numerous new (or perceived as new) phenomena, the theology of spirituality, as a scholarly area examining spiritual experience, is becoming a branch of theological research of increasing importance. The first part of this article focuses on the ever-growing areas of interest found within the theology of spirituality, a growth stemming from the core of the field itself (agere sequitur esse). The second part emphasizes the newer areas of interest within the theology of spirituality. These new horizons arise from the pluralism of theology itself and the criteria used in differentiating theological disciplines, such as ethno-geographic, doctrinal, and ascetic-practical concerns. In particular, amid a fast-changing world in which information and mutual contact have become incredibly accessible, the interpenetration of cultures and traditions can not only be of great value but also carry the dangers of a chaotic eclecticism. As this accessibility becomes ever easier and more pervasive, contemporary human beings can thus become confused, not only about their worldviews but also concerning their spiritual and religious beliefs. Thus, research into the theology of spirituality is becoming increasingly more important.